2021
DOI: 10.1007/s00405-021-06954-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraepithelial capillary loops and atypical vessels in confocal laser endomicroscopy for the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma

Abstract: Purpose Confocal laser endomicroscopy (CLE) allows surface imaging of the laryngeal and pharyngeal mucosa in vivo at a thousand-fold magnification. This study aims to compare irregular blood vessels and intraepithelial capillary loops in healthy mucosa and squamous cell carcinoma (SCC) via CLE. Materials and methods We included ten patients with confirmed SCC and planned total laryngectomy in this study between March 2020 and February 2021. CLE images of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Overall, the images within our study showed an increased number of blood vessels in the lip mucosa. However, there were no malignant features of the vascular structure (like corkscrew-like vessels or dilated intraepithelial capillary loops) as described in a previous study by our research group [ 21 ]. This supports the assumption that these are physiological mucosal areas, consistent with the clinical appearance (even without histological confirmation).…”
Section: Discussionmentioning
confidence: 45%
“…Overall, the images within our study showed an increased number of blood vessels in the lip mucosa. However, there were no malignant features of the vascular structure (like corkscrew-like vessels or dilated intraepithelial capillary loops) as described in a previous study by our research group [ 21 ]. This supports the assumption that these are physiological mucosal areas, consistent with the clinical appearance (even without histological confirmation).…”
Section: Discussionmentioning
confidence: 45%
“…In a previous study about the diagnostic value of intraepithelial capillary loops and atypical vessels in SCC diagnosis, we demonstrated that a cutoff value for vessel diameter of 30 μm enables the diagnosis of SCC with a sensitivity and specificity of, respectively, 90.6% and 71.3% [ 29 ]. However, while both criteria, tissue homogeneity and vessel diameter, as stand-alone diagnostic features, provide good sensitivity and specificity values, its diagnostic metrics are still inferior to diagnostic scores that integrate both features [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…White et al first described the applicability of CLE in the head and neck region in 1999 using six healthy control tissue specimens and described its morphological similarity with corresponding H&E-stained microscopic sections [ 54 ]. This first description of CLE imaging in the head and neck area was followed by numerous in vitro [ 55 , 56 , 57 , 58 , 59 , 60 ] and in vivo studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] focusing on the noninvasive detection of head and neck cancer using CLE. Table 2 gives an overview of the most important in vitro and in vivo studies on CLE applications in the head and neck region over the past 23 years.…”
Section: Cle On Ent Applicationsmentioning
confidence: 99%
“…From 2016 on, systemically applied fluorescein (i.v. application) was used in nearly all published CLE in vivo studies in the head and neck region and presumably provides the best tissue contrast and quality of generated CLE images [ 81 , 82 , 83 , 84 , 88 , 89 , 90 , 91 ]. Further studies have to show if other fluorescent dyes, e.g., indocyanine green, can potentially enhance tissue contrast even more.…”
Section: Cle On Ent Applicationsmentioning
confidence: 99%
See 1 more Smart Citation